P111 SMILE: Sustaining Medical Education In a Lockdown Environment. Student perceptions of a free online access medical education platform as an adjunct to the traditional undergraduate curriculum during lockdown. (8th April 2021) - Pascoe, John; Foster, Paul; Quddus, Muntasha; Kosti, Angeliki; Guest, Francesca; Stevens, Sian; Bamford, Richard; Coulston, James; Pascoe, John
Abstract: Introduction: The coronavirus outbreak has had significant impact on medical students worldwide. SMILE is a free online access medical education (FOAMed) platform. SMILE delivered 200 lectures during lockdown with up to 1400 students per session from both UK medical schools and 33 abroad. Here we discuss student perceptions to SMILE during lockdown Method: An electronic survey was used to collect information from students who had utilised the platform during lockdown. This examined access to learning, impact on their mental health during lockdown and the differences between FOAMed and more traditional based campus lecture based learning. Results: 1306 students responded to the anonymous survey with 94% of students stating SMILE had been "extremely useful" or "very useful" at supplementing learning during covid. 71% of students stated lockdown had affected their stress levels and 44% reported deterioration in their mental health. >80% felt SMILE improved stress levels by adding structure and providing motivation. Students attended 4.3hours/week of university teaching, vs 7.9hours/week by SMILE. Positives included: anonymity, making 80% more likely to both ask and answer questions, the informal approach, ease of access and enthusiastic teachers. Negatives included time differences and technical issues such as poor Internet. 98% stated they would be interested in future SMILE projects post lockdown Conclusions: SMILE addressed challenges identified during an unanticipated transition towards the online provision of medical education on an international scale. Students found SMILE lectures effective, accessible and safe, supporting FOAMed as part of the "new normal" post lockdown